2017
DOI: 10.1186/s40337-017-0174-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cognitive-behavioral exposure-based body image therapy for overweight females with binge eating disorder: a pilot study

Abstract: BackgroundAlthough not part of the diagnostic criteria of the DSM-5, body image disturbance seems to be a relevant feature of Binge Eating Disorder (BED) as well as of other eating disorders such as Anorexia Nervosa (AN) or Bulimia Nervosa (BN). Hence, the aim of the present pilot study was to assess the changeability of body image disturbance in a sample of overweight females with BED by a cognitive-behavioral treatment, directly addressing body image disturbance.MethodOverweight females (N = 34) with BED wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 97 publications
0
22
0
1
Order By: Relevance
“…Our study differs from and adds to previous findings by investigating the association between FA and body uneasiness, while controlling for potential confounding variables. Our results suggest that clinicians should carefully investigate the presence of body uneasiness in individuals with FA symptoms in order to use specific treatment approaches, such as cognitive‐behavioural exposure‐based body image therapy (Lewer et al, ), to manage this critical symptom.…”
Section: Discussionmentioning
confidence: 96%
“…Our study differs from and adds to previous findings by investigating the association between FA and body uneasiness, while controlling for potential confounding variables. Our results suggest that clinicians should carefully investigate the presence of body uneasiness in individuals with FA symptoms in order to use specific treatment approaches, such as cognitive‐behavioural exposure‐based body image therapy (Lewer et al, ), to manage this critical symptom.…”
Section: Discussionmentioning
confidence: 96%
“…As the empirical evidence referring to these aspects is still relatively scarce for individuals with BED, it is not yet clear whether individuals with BED are also influenced by cognitive biases, body size misperception, or checking and avoidance behavior. Nevertheless, Williamson et al [ 56 ] propose that a cognitive bias leads to increased negative emotions and dietary restraint, which is both common in individuals with BED [ 62 , 67 , 68 , 87 ] and in turn might lead to binge eating behavior. Furthermore, there are signs that overvaluation of weight/shape triggered by body-related stimuli, such as watching other persons in a fashion store, might further increase the desire to binge in individuals with BED [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the overall sample size was rather small and the proportion of participants with BED was only about 6%, conclusions regarding the treatment of BED need to be drawn with caution. In a recent study that explicitly addressed body image disturbance in BED, Lewer and colleagues [ 62 ] compared individuals with BED and obesity to a waiting-list control group within a standardized group therapy program consisting of ten sessions. During the program, participants received psychoeducation on the disorder, were guided in cognitive restructuring of negative cognitions towards one’s own body, exposed themselves to their body in the mirror, and received guidance regarding exposure outside of the therapeutic setting (e.g., use personal care products such as body lotion, visit a public pool).…”
Section: Treatment Of Body Image Disturbance In Binge Eating Disormentioning
confidence: 99%
See 1 more Smart Citation
“…The study shows that body image therapy is a worthy complement to the current approaches for BED treatments, as it significantly lowers the dysfunctional cognition related to body and self-esteem (Legenbauer, Schütt-Strömel, Hiller, & Vocks, 2011). The same manualized treatment was used in another research study where 15 overweight female participants with BED showed significant improvement in the cognitive-affective component of body image disturbance (one's mental picture of oneself) compared to the obese women in the control group who did not receive the treatment (Lewer, Kosfelder, Michalak, Schroeder, Nasrawi, & Vocks, 2017).…”
Section: Body Image Therapy and Eating Disordermentioning
confidence: 96%